Asimetrías de información entre agente y principal de las universidades chilenas (2012)
This research work is aimed at determining whether there are any informational asymmetries between the presidents and the members of collegial bodies in Chilean universities. The framework of agency theory, in which the president of a university plays the role of agent while the collegial body serves as principal, assumes that this kind of asymmetry exists. The methodology was based on a closed-ended questionnaire where respondents had to demonstrate their knowledge of supposedly basic topics related to management performance. The results provide compelling evidence confirming the agency theory, which contends that an agent holds more information than a member of a collegial body, and, if internal, the member’s knowledge exceeds that of external members.